A Comparative Study Between the Goldmann Applanation Tonometer and the Non-Contact Air-Puff Tonometer (Huvitz HNT 7000) in Normal Eyes - Stock RA (Dove Medical Press, 2021)
Ricardo Alexandre Stock, Carine Ströher, Rodrigo Rosa Sampaio, Rafael André Mergener, Elcio Luiz Bonamigo Medical School of the University of the West of Santa Catarina (Universidade do Oeste de Santa Catarina – UNOESC), Joaçaba, Santa Catarina, BrazilCorrespondence: Ricardo Alexandre Stock Belotto Stock Centro Oftalmológico, Rua Rio Branco, 589, Centro, CEP: 89, Joaçaba, SC, 600-000, BrazilTel + 55 49 35220788Fax + 55 49 35225059Email ricardostockreal@gmail.comObjective: To assess whether the non-contact air-puff tonometer (NCT) is an appropriate alternative to the Goldmann applanation tonometer (GAT) for measuring intraocular pressure (IOP).Patients and Methods: An observational, cross-sectional, and comparative study with a quantitative approach was carried out. Two techniques for IOP measurements using the standard GAT and the NCT were compared. A total of 180 eyes from 90 patients were included in the study.Results: The total mean IOP according to NCT measurements was 14.12 mmHg, and the total mean IOP according to the GAT was 12.98 mmHg; these values were significantly different (p=0.0018). When dividing the participants into three groups according to the measurement range obtained and comparing the mean NCT and GAT measurements in each group, in Group 1 (10– 15 mmHg), no statistically significant difference was found between the means of the two tonometers (p=0.3100), a difference was observed between Group 2 (16– 19 mmHg) and Group 3 (20 mmHg or more) (p< 0.001). When dividing the participants by age group, the means obtained by the two tonometers also differed significantly between Group 4 (40– 59 years) and Group 5 (60 years or more) (p< 0.0001). In all groups, the mean measurements by the NCT were higher than those by the GAT.Conclusion: The NCT presented an approximate mean of the measures with the GAT in group 1 but was overestimated in the measurements of the groups 2 and 3.Keywords: ocular tonometry, glaucoma, ocular hypertension, intraocular pressure, efficiency